PENGARUH BAHAN BAKU DAN PEREKAT UREA-FORMALDEHIDA TERHADAP SIFAT-SIFAT PAPAN SERAT - Rena M Siagian; Bambang Wiyono (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
Properties of hardboard are not only effected by the raw material used and the basic manufacturing process employed but influenced by subsequent processing of treatment such as gluing, impregnation, heat treatment and oil tempering. The purpose of the research is to study the effect of raw material and urea-formaldehyde adhe11ive on hardboard properties. The raw material comprise of yute (Corchorus capsularis L), rosella (Hibiscus sabdariffae L), kena; (H. cannabinus), linum (Linum usitatissimum L), dan lamtorogung (Leucaena leucocephalla). The level of the urea-formaldehyde adhesive incooperated in the experiment were 0 and 1.5 per cent based on oven dry pulp.The results indicate that the raw material used for hardboard making has a significant effect on pulp yield, alkali consumption, water absorption, tensile strength parallel to surface, and modulus of rupture. Tensile strength parallel to surface of hardboard was significantly effected by adding urea-formaldehyde adhesive. The hardboard made of kenaf has the highest tensile strength parallel to surface, and modulus of rupture, and high water absorption. For decreasing the latest properties, perhaps phenol formaldehyde. can be added to the stock.